The Tuberculosis Epidemic in Romania : TB Allocative Efficiency Model Findings and Recommendations - Socaci, Adriana; Mahler-Boca, Beatrice; Chiotan, Domnica Ioana; Popescu, Gilda; Stefan, Mihaela; Cioran, Nicoleta; Benedikt, Clemens; Cheikh, Nejma; Fraser, Nicole; Shubber, Zara; Abeysuriya, Romesh; Kedziora, David; et al. (World Bank, Washington, DC, 2019)
This report summarizes the findings of an allocative efficiency study of Romania’s Tuberculosis (TB) response, which was conducted using the Optima-TB model. The analysis was conducted to support Romania in its decision-making on strategic TB investments during the current National Strategic Plan for the Control of Tuberculosis in Romania (NSP, 2015‒20) and up to 2030. The analysis highlights the potential for Romania to maximize its impact on the TB response by reallocating spending on unnecessary hospitalization to increase the coverage of ambulatory care, treatment of drug-resistant TB and enhanced and active case finding in congregate community settings and high-risk areas.